Pengaruh Motivasi dan Penggunaan Aplikasi Papan Tulis Online Serta Aplikasi Jamboard Terhadap Perkembangan Motorik Anak Usia Dini - Muslimah, Muslimah; Putri, Dewi Artati Padmo; Kusdianto, Kusdianto (Nusantara: Jurnal Pendidikan Indonesia, 2024)
Purpose – The very rapid development of science and technology has an impact on every part of life, including the world of education. Using online whiteboard applications and interactive Google Jamboard can train children to write, draw, and color in Early Childhood Education classes. This research aims to determine the influence of motivation and use of online whiteboard applications and jamboard applications on the motoric development of PAUD children.Method – This research used a quasi-experiment with a nonrandomized control group pretest-posttest design. The samples taken were 14 PAUD children at the YPJ Tembagapura school and 14 PAUD children at the YPJ Kuala Kencana school, Mimika Regency. Data collection used observation techniques and questionnaires with a Likert scale.Findings – Based on the results of the Friedman Test, there is an influence of motivation and learning with online whiteboard applications on the motoric development of PAUD children. Based on the results of the Friedman Test, there is an influence of motivation and learning with the Google Jamboard application on the motoric development of PAUD children. Based on the results of the Paired Samples t-Test, there is a significant difference in motivation and learning between the Google Jamboard application and the online whiteboard application on the motoric development of PAUD children in Mimika Regency. Research Implications – The study's generalizability is constrained by the small sample size of 28 PAUD children from specific schools in Mimika Regency, potentially limiting the applicability of findings to a broader population or diverse educational settings.